Rural population growth, agricultural change and natural resource management in developing countries: a review of hypotheses and some evidence from Honduras - Pender, John L. (International Food Policy Research Institute, 1999)
This paper reviews hypotheses about the impacts of rural population growth on agriculture and natural resource management in developing countries and the implications for productivity, poverty, and natural resource conditions. Impacts on household and collective decisions are considered, and it is argued that population growth is more likely to have negative impacts when there is no collective responses than when population growth induces infrastructure development, collective action, institutional or organizational development. The impacts of population pressure, particularly on natural resource conditions, may be very different in different contexts, depending on the nature of local markets, institutions, and other factors. Thus careful and comparative empirical work is needed in different contexts before general conclusions can be drawn. There is still a lack of such empirical evidence. The results of one study in central Honduras are used to examine some of the hypotheses presented. The results support neo-Malthusian concerns about the effects of population growth on land degradation, but also provide some support to Boserupian predictions that population pressure will induce adoption of labor-intensive land improvements, collective action to manage natural resources, and organizational development. In general, however, the impacts of population pressure were found to be relatively small and other factors, including infrastructure development and technical assistance programs, had stronger impacts on agricultural change and natural resource management. Although induced innovation theory argues that population pressure may induce such policy responses, we found that these interventions were more likely in less-densely populated communities. This emphasizes that such “induced” policy responses to population pressure do not happen automatically.